An EGFP-marked recombinant lactobacillus oral tetravalent vaccine constitutively expressing α, ε, β1, and β2 toxoids for Clostridium perfringens elicits effective anti-toxins protective immunity. Issue 1 (1st January 2019) - Ding, Guojie; Bai, Jing; Feng, Baohua; Wang, Li; Qiao, Xinyuan; Zhou, Han; Jiang, Yanping; Cui, Wen; Tang, Lijie; Li, Yijing; Xu, Yigang
ABSTRACT: Clostridium perfringens is a common opportunistic pathogen endangering livestock and poultry breeds. Here, using enhanced green fluorescent protein as screening marker, a recombinant lactobacillus tetravalent vaccine constitutively expressing α, ε, β1, and β2 toxoids of C. perfringens was developed, and its immunogenicity in mice was investigated via oral administration. This probiotic vaccine could effectively induce antigen-specific secretory IgA (sIgA)-based mucosal and IgG-based humoral immune responses, and significantly high levels ( p < 0.05) of cytokines IL-2, IL-4, IL-10, IL-12, IL-17, and IFN-γ were produced in immunized mice. Moreover, lymphoproliferation and percentage of CD4 + and CD8 + T cells significantly increased in mice of the probiotic vaccine group. Challenge experiments were performed in mice with C. perfringens toxinotypes A, C, and D crude toxins to evaluate protection efficiency of the probiotic vaccine, using a commercial inactivated C. perfringens vaccine made by C. perfringens toxinotypes A, C, and D as vaccine control. We observed 80% protection rate in the probiotic vaccine group, which was higher than commercial vaccine group, whereas all mice in control groups died and obvious histopathological changes were observed in liver, spleen, kidney, and intestines of mice. Significantly, we compared the immunogenicity and protection efficiency of lactobacillus constitutive expression system and lactobacillus inducible expression system, and results showed that lactobacillus constitutive expression system has obvious advantages. Our study clearly demonstrated that the probiotics vaccine could effectively induce mucosal, humoral, and cellular immunity, and provide effective protection against C. perfringens toxins, suggesting a promising strategy for the development of oral vaccine against C. perfringens .